Witchcraft Accusation and the Challenges Related Thereto: Can South Africa Provide a Response to this Phenomenon Experienced in Tanzania? - Annie Singh; Norah Hashim Msuya (Obiter, 2019)
Witchcraft accusation is among the cultural beliefs that infringe women’s rights in Tanzania. Women in Tanzania are disproportionately accused of witchcraft compared to their male counterparts. These beliefs have led to intimidation, psychological isolation, abuse, violence and in extreme cases the killing of women who are accused of witchcraft whenever a natural disaster befalls the community. This article examines the gender-based nature of witchcraft accusation and the conditions that have led to the vulnerability of women due to this practice in Tanzania. It also examines how the Tanzanian legal system has dealt with the challenges of witchcraft accusation to date. A reflection on the stance maintained by the South African Law Commission in addressing this problem is considered. This has been necessary to determine whether there are any practical solutions that may be emulated or adapted by the Tanzanian Reform Commission. The article concludes that it is the duty of the State, regardless of people’s political, economic and cultural beliefs, to protect all human rights and fundamental freedoms. The law in Tanzania should therefore be reformed to ensure that the gender-violence phenomenon is adequately addressed. It is also submitted that it is necessary for the law to address witchcraft accusation practices across the African continent.